2009
DOI: 10.1017/s1041610209008527
|View full text |Cite
|
Sign up to set email alerts
|

Nature, prevalence and factors associated with depression among the elderly in a rural south Indian community

Abstract: Background: Depression in old age is an important public health problem causing considerable morbidity and disability worldwide. There is a dearth of community studies from India investigating geriatric depression and its associated risk factors. This study aimed to establish the nature, prevalence and factors associated with geriatric depression in a rural south Indian community.Methods: We recruited 1000 participants aged over 65 years from Kaniyambadi block, Vellore, India. We assessed their socio-demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
141
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(166 citation statements)
references
References 29 publications
21
141
3
1
Order By: Relevance
“…This finding is corroborative with the study conducted by Blazer et al [53]. Nevertheless, some other studies from Indian communities showed higher prevalence of depression with increasing age [26,27]. It is clearly demonstrated in the present study that rural and urban elderly differ significantly in the prevalence of depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is corroborative with the study conducted by Blazer et al [53]. Nevertheless, some other studies from Indian communities showed higher prevalence of depression with increasing age [26,27]. It is clearly demonstrated in the present study that rural and urban elderly differ significantly in the prevalence of depression.…”
Section: Discussionsupporting
confidence: 93%
“…A cross-sectional study in South India has revealed 21.7 percent of total elderly aged 60 years and above with depressive systems (36.0 percent were males and 64.0 percent were females) and prevalence of cognitive impairment was higher among the depressive individuals [25]. A study related to the nature, prevalence and factors associated with depression among rural South Indian community found poverty and physical ill health were the risk factors for the depression even when good social support was available [26]. Lower prevalence of depression was associated with higher standards of living, matriarchal family and a high female literacy rate and higher prevalence of depression was associated with unemployed, illiterate, housewife and widow in rural South India [27].…”
Section: Diagnostic and Statistical Manual Of Mental Disorders [Dsm Imentioning
confidence: 99%
“…11,39 Age and chronic medical conditions were also significantly predictive of depressive symptoms in both bivariate and multivariate analyses, consistent with prior studies. 40,41 Some studies have indicated that the prevalence of depression declines from midlife to older adulthood. 27 This was partially supported in the current study, as the quadratic age trend indicated that the odds of moderate depressive symptoms declined somewhat from age 60 to 72 and only increased thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…12 With an absolute precision of 4.5 % and confidence level of 95 %, it was estimated that the minimum required sample size was 406 subjects. Allowing for a 20 % non-response, the minimum sample needed for the study was increased to 466 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…8 Published studies reveal that prevalence of depression among elderly in developing countries ranges from 5.22 to 45.9 %. [9][10][11][12][13][14][15][16][17][18][19] Recent estimates indicate that, in India, depression results in loss of 961,000 disability adjusted life years (DALYs) per year among elderly. 20 As depression is potentially treatable condition, a significant reduction in DALYs is expected.…”
Section: Introductionmentioning
confidence: 99%